2011
DOI: 10.1007/s12178-011-9099-2
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spine: degenerative conditions

Abstract: Degenerative cervical spine disorders will affect up to two-thirds of the population in their lifetime. While often benign and episodic in nature, cervical disorders may become debilitating resulting in severe pain and possibly neurologic sequelae. Non-operative treatment continues to play an important role in treating these patients, with medications, therapy and interventional pain injections playing increasing roles in treatment. Surgical treatment including anterior and posterior decompression and fusion h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 43 publications
0
48
0
2
Order By: Relevance
“…Degenerative cervical spine disease occurs during the lifetime in more than two-thirds of the overall population [14]. Although the precise prevalence of degenerative cervical kyphosis has not been reported, one study reported that the prevalence of cervical kyphosis was 66% in a population of typical 30- to 50-year-old adults [15].…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative cervical spine disease occurs during the lifetime in more than two-thirds of the overall population [14]. Although the precise prevalence of degenerative cervical kyphosis has not been reported, one study reported that the prevalence of cervical kyphosis was 66% in a population of typical 30- to 50-year-old adults [15].…”
Section: Discussionmentioning
confidence: 99%
“…Many cases of axial neck pain are temporary and will resolve with time and nonoperative treatment. 1 It can be difficult to distinguish between an acute or chronic condition related to work and the chronic pain and degeneration associated with aging. Cervical degenerative disc disease (DDD) is a common cause of pain and disability, affecting approximately two-thirds of the US adult population.…”
Section: Background and Prevalencementioning
confidence: 99%
“…Cervical degenerative disc disease (DDD) is a common cause of pain and disability, affecting approximately two-thirds of the US adult population. 1 Most symptomatic cases present between the ages of 40 and 60, 2 although many individuals never develop symptoms. MRI studies have documented the presence of DDD in 60% of asymptomatic individuals aged greater than 40 years and 80% of patients over the age of 80 years ( Figs.…”
Section: Background and Prevalencementioning
confidence: 99%
“…In the last decade there have been several studies that have evaluated whether C-ADR leads to fewer complications, better in multi-level clinical outcomes and more patients' satisfaction than ACDF. Little attention has been paid to pain outcomes in systematic reviews of these studies despite the fact that cervical degenerative disc disease results in significant pain and disability [1].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical disease prevalence increased with aging and as a consequence to chemical and structural changes in the disc. These changes lead to neck and arm pain which is usually associated with radiculopathy and myelopathy [1]. The radiculopathy is a neurological condition caused by the compression or irritation of the spinal nerves when they exit the spine.…”
Section: Introductionmentioning
confidence: 99%